PUBLIC PERCEPTIONS AND TRUST IN BATIK SOLO TRANS: A TWO-WAY SYMMETRICAL COMMUNICATION PERSPECTIVE - Nabila Naura Mufida Arifin; Cendrawasih Wahyuning Djati; Tiara Aulia Yasmin; Femas Hazel Ferdinand (Indonesian Journal of Digital Public Relations (IJDPR), 2026)
In Surakarta, Batik Solo Trans (BST) is the foundation of social movement and urban identity. The recent subsidy cuts and modifications to operations have, however, compromised the quality of services, decreasing the trust of the public. In this paper, the perception of people is studied to develop a rebranding strategy based on Two-Ways Symmetrical Communication and The Perspective-Taking of “If I Were Them” theory. The data collection was based on a case study design, in which online questionnaires were utilized to gather data between November and December 2025, covering 32 purposely-selected respondents in the Greater Surakarta area. Descriptive quantitative data analysis indicates that, although staff professionalism is valued, route inaccessibility (65.6%) and unpredictable schedules are the main obstacles to use. Also, it has been found out that there is still significant one-sided communication among the operator and the people. The research concludes that visual rebranding is not enough; regaining trust involves a strategic move that would focus on a Two-Way Symmetrical Communication and Perspective-Taking in line with the real needs of the user. This finding offers a framework on how the Department of Transportation can make BST a more participatory and community-oriented service.